On the possibility of correlating the Oedometric curve to the Atterberg limits and the natural water content of clays, a laboratory study on Bangkok clays - Somchai Jittavisuttivong; Tomiolo, Andrea; Balasubramaniam, A.S.; Prinzl, Frediric; Government of Australia (Bangkok : Asian Institute of Technology, 1982)
This thesis presents the possibility of correlating the Oedometric curve to the Atterberg limits and the natural water content of clay, studied on Bangkok clay Fifteen series of tests, consisting of Index Properties Determination, Consolidation and CIU Triaxial Test were performed on undisturbed samples, taken from 3.00 m. below the existing ground level at Don Muang Airport site. The test results were collected in Table 3.1 Compression index or Compression ratio, determined as the inclination of the steepest part of the load compression curves, was plotted with liquid limit, natural water content and initial void ratio. These relationships were compared with the previous or published correlations and were studied only in the simple linear model. Any previous correlation that coincided with the test results was considered and then modified by using the sum of the least square method in order to represent the results. Deviation of the test results are determined by using a % error band compared to the modified equations. It is found that all the test results are included within a ±20% band of error. It can also be concluded that the value of Su/Pc of the soil related to plasticity index better than to Su/P. when compared to the Skempton's line.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering, School of Engineering and Technology
Thesis (M. Eng.) - Asian Institute of Technology, 1982
Keywords: Clay -- Thailand -- Bangkok -- Testing